PHENOMENOLOGY OF THE POWER – GENESIS OF FORMS OF MANIFESTATION OF THE GLOBAL SYSTEM CONTRADICTION 'CREDITORS – DEBTORS' - Vyacheslav I. Karpunin (Plekhanov Russian University of Economics, 2017)
In article on the basis of the new concept of design and functioning of social and economic mechanisms developed by authors the system relationships of cause and effect causing variety of forms of life of a global system contradiction ′creditors reveal there are debtors′. The mechanism providing expansion of a system contradiction as authors of the concept believe consists of three mutually caused components: institutional, tool and procedural. This triple system unity, making a necessary and sufficient basis of functioning of social and economic mechanisms, generates the corresponding diverse historical forms of social, economic and political life of a system contradiction ′creditors there are debtors′. The methodological basis of the analysis (variety of forms of life of a system contradiction), despite the seeming independence of each separate phenomenon mentioned by us in article, allows to reveal deep bases of their interrelation and interdependence, to understand the uniform nature of these phenomena and to slightly open thereby the mysteries of ′metaphysics of the power′. From variety of the significant phenomena (we mention some of them in article) only two, already belonging stories of the 21st century are noted: accident (on September 11, 2001) and celebration (on October 9, 2009). What can unite two so diverse in a form and contents, the sphere of life of the phenomenon? Money, very big money. Money as an effective financial instrument of the political, economic power, social influence and violation of moral laws, money as the universal requirement of a part of public wealth predetermine models and mechanisms of behavior of the world managing director of elite, first of all by means of institutes of the world ′financial government′ today. A time of representatives of this elite, after Paul Krugman - professor of the Princeton university (USA), the Nobel Prize laureate of economy, call ′very big people′. Perhaps, it and traditional participants of Bilderbergsky club, first of all members of his Advisory committee (Advisory Committee) consisting approximately of ten people. As the encyclopedia Britannica reports, it ′those who exert impact on national policy and the international affairs′. This elite has appropriated the boundless right to decide destinies of the world. The 21st century young still already abounds with diverse phenomena - forms of manifestation of a global system contradiction ′creditors - debtors′. Sometimes, unfortunately, it is tragic, an infinite number of times tragic events. To judgment of system interrelation of key phenomena - phenomenology of the power and that the same, ′creditors - debtors′ - this article is also devoted to phenomenology of a global system contradiction.